Enhanced performance of tin halide perovskite solar cell by addition of lead thiocyanate. Issue 25 (16th April 2018) - Gao, Fengqiang; Li, Chunhai; Qin, Liang; Zhu, Lijie; Huang, Xin; Liu, Huan; Liang, Liming; Hou, Yanbing; Lou, Zhidong; Hu, Yufeng; Teng, Feng
Abstract : The MASnI3 -based PSCs with an efficiency of 6.02% was fabricated by incorporating 20 mol% of Pb(SCN)2 . Abstract : Organic–inorganic hybrid halide perovskites have attracted great attention as a new type of photovoltaic materials. However, lead (Pb) perovskite solar cells (PSCs) would cause environmental pollution in future large-scale applications. Therefore, it is imperative to find environmentally-friendly metals to replace lead. Although tin (Sn) halide perovskites can be regarded as a valid alternative to lead perovskites, their poor stability and lower conversion efficiency hinder the substitution of Sn for Pb. In this work, highly uniform and pinhole-free perovskite films were prepared by the introduction of a small amount of lead thiocyanate in precursor solutions. The CH3 NH3 SnI3 (MASnI3 ) films with Pb additive show an absorption edge of 950 nm. Besides, lead ions can depress the LUMO energy level of Sn-based perovskite materials, which is a benefit to an increase in the opencircuit voltages of PSCs. Consequently, the enhanced performance was achieved in the PSCs based on MASnI3 with a fill factor of 66%, open circuit voltage of 0.54 V and maximum power conversion efficiency of 6.03%.